Kompetensi Profesionalisme Guru dalam meningkatkan Kualitas Hasil Belajar Siswa pada Aspek Pengetahuan Siswa - Agnes Natalia Sihombing; Dewi Wulandari; Enjelita Dwi Maharani; Fahira Silva Dilla Nasution; Theresia Mardiyana Tamba; Jamaludin Jamaludin (International Forum of Researchers and Lecturers, 2025)
This study explores the relationship between teacher professionalism and student learning outcomes in Civic Education at SMP Muhammadiyah 1 Medan. It focuses on how teacher participation, teaching activities, and challenges influence the learning process. A qualitative descriptive approach was used, with data collected through interviews and surveys. The findings reveal that teachers' professional competencies, particularly in lesson planning, the use of varied teaching media, and providing remediation, significantly improved students' knowledge acquisition. Despite challenges such as curriculum changes and limited resources, teachers like Ibu Monalisa Tarigan, S.Pd actively engage in professional development programs to enhance their teaching effectiveness. The study highlights the importance of teacher preparation, creativity, and individualized attention in creating a productive learning environment. It concludes that teacher professionalism has a positive impact on both cognitive and creative student outcomes.